EFFECT OF ETHANOLIC ROOT AND TWIG EXTRACTS OF VERNONIA AMYGDALINA (ETIDOT) ON LIVER FUNCTION PARAMETERS OF STREPTOZOTOCIN INDUCED HYPERGLYCAEMIC AND NORMAL WISTAR RATS - U.O., Luke; P.E., Ebong; E.U., Eyong; A.E., Robert; S.U., Ufot; G.E, Egbung (European Scientific Journal, ESJ, 2013)
The effects of various concentrations of ethanolic extracts of Vernonia amygdalina (VA) stem and root on some biochemical indices of liver function in streptozotocin-induced diabetic and non-diabetic rats treated with 200mg/kg b.w and 400mg/kg b.w was determined. LD50 value of 1000 mg/kg was established. The oral administration of the extracts lasted for 28 days. The rats were divided into five parallel groups of non-diabetic and diabetic rats, with six rats in each group. Group 1 received Dimethy sulfoxide(DMSO) and served as the negative control. Group 2 received 200mg/kg b.w Vernonia amygdalina (stem), group 3 received 400mg/kg b.w Vernonia amygdalina (stem). Group 4 received 200mg/kg b.w Vernonia amygdalina (root). Group 5 was given 400mg/kg b.w Vernonia amygdalina (root). Both stem and root extracts (200 and 400) mg/kg b.w significantly improved body weight and reduced whole blood glucose levels to normal but not up to hypoglycaemic level in diabetic treated rats. Total protein and albumin in serum were increased in diabetic rats treated with stem (200 and 400) mg/kg b.w respectively. The findings suggest that V. amygdalina ethanolic stem and root extracts is hepatoprotective in diabetic rats and may be of nutritional/ clinical relevance amongst African populations for treatment of different ailments.